Formation of Readiness of the Future Primary School Teachers to the Organization of the Individual Activity of Pupils - Halus, Oleksandr; Kohut, Alona (Pedagogical Discourse, 2017)
The article analyses theoretical approaches to the interpretation of the concept «readiness of the future primary school teachers». The urgency of the considered problem in the Concept of the New Ukrainian School, the State Standard of Primary General Education has been mentioned. The possibilities of using various forms, methods, means and methods of organizing individual work with junior pupils at the lessons and out of school have been revealed. The emphasis is on the study by the future teachers of primary school of the disciplines in the context of organization of individual work with pupils. The attention is paid to the introduction of the training of the future teachers of primary school the special course «Organization of Individual Work of Pupils in Primary School». It will enable the future teachers of primary school to acquire knowledge, skills and abilities as for the organizing and pedagogical management in the individual work of junior pupils during academic and extra-curricular time as a factor of the development of their abilities, activity, autonomy and creativity.